The Impacts of Country Risk, Global Economic Policy Uncertainty, and Macroeconomic Factors on the Turkish Tourism Industry - Irani, Farid; Athari, Seyed Alireza; Al Al Hadood, Abobaker (Routledge Journals, Taylor & Francis Ltd, 2022)
This study investigates the impacts of country-specific risk, namely, political and economic risks, global economic policy uncertainty, and also macroeconomic factors on the price of Turkish tourism firms' stocks during the 2000 to 2017 period. By considering the structural break, the results underscore that a rise of political and economic risks, global economic policy uncertainty, and real exchange rate correspond with decreasing stock prices in the long-run. Moreover, the short-run results show that the real exchange rate and global economic policy uncertainty impact stock prices negatively though stock prices react positively to a rise of political risk. To the best of our knowledge, this is the first study that attempted to conduct this nexus, and findings have important implications for managers, investors, and assets analysts.
Keywords: Stock price; political risk; economic risk; global economic policy uncertainty; tourism firms; Turkey